PENERAPAN AKUNTANSI PADA UMKM: PASAR TIBAN DEMAK - Annisa Auliya Handini; Itsna Zaairotul Mufarihhah (Universitas Duta Bangsa Surakarta, 2025)
The low level of accounting knowledge among MSMEs is often an obstacle in developing their businesses. The role of the government is very important in conveying accounting information effectively and easily understood so that MSMEs can grow. The government needs to be more active in socializing and educating about taxation. Understanding simple financial reporting is also important so that MSMEs can easily gain access to funding. Continuous accounting education is needed to strengthen the position of MSMEs in the national economy. This study uses a quantitative approach with a closed questionnaire to test hypotheses and measure the relationship between variables. Financial literacy is defined as a combination of awareness, knowledge, skills, attitudes, and behavior to make informed financial decisions. Financial access is the ability of individuals or business actors to obtain formal financial services and products easily, quickly, and affordably. MSME growth is defined as an increase in business capacity in terms of production, quality, marketing, and income. The results of the study showed that financial access has a positive and significant effect on MSME growth (coefficient 0.550, p 0.000). Financial literacy has also been shown to have a positive and significant effect on MSME growth (coefficient 0.434, p 0.000). These two independent variables contribute significantly to driving the growth of MSMEs. As much as 77% of the variation in MSME growth can be explained by financial access and financial literacy.